Beyond Credibility of Doing Business in China: Strategies for Improving Corporate Citizenship of Foreign Multinational Enterprises in China - Lam, Maria Lai-Ling (Journal of business ethics, 2009)
This study examines the perceptions of Chinese executives concerning corporate social responsibilities in their Chinese subsidiaries of foreign multinational corporations in China. These Chinese subsidiaries are found in the elementary stage of corporate citizen development even though their headquarters are in the advanced stage. The key challenges of moving Chinese subsidiaries to be better corporate citizens in China are specific Chinese business culture, intellectual property rights, internal due process, insufficient Chinese government support, and lack of knowledge of Chinese subsidiaries. Through this study, foreign multinational corporations need to invest in social capital that facilitates the transfer of knowledge of comprehensive corporate responsible practices from the headquarters to their Chinese subsidiaries, and to encourage their Chinese subsidiaries to be more actively engaged with external business partners that support corporate social responsibility.